Retrofit Approach in Palm Oil Refining by Implementing Pinch Analysis (A Case Study at Sahabat Oil Products (SOP), Lahad Datu, Malaysia) - Lidu @ Serirama, Seri Rahimah (IRC, 2016)
Palm Oil industry is one of the major contributors of Malaysia’s economic growth. Being the largest Crude Palm Oil (CPO) producer in the world after Indonesia, Malaysia holds an important niche in fulfilling the growing demand for oil and fats products. This industry is probable for energy saving opportunities especially in physical refining of the oil products which involve energy intensive units. Heat integration analysis in refining of palm oil in Sahabat Oil Products (SOP), Lahad Datu was conducted and presented in this project work.